2018
DOI: 10.1016/j.joca.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcription factors responsible for dysregulated networks in human osteoarthritis cartilage by global gene expression analysis

Abstract: We identified a novel subnetwork of dysregulated TFs that represent new mediators of abnormal gene expression and promising therapeutic targets in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(189 citation statements)
references
References 62 publications
12
177
0
Order By: Relevance
“…Other predicted ECM genes bound by FoxO1 ( COL3A1 , COL5A2 ) and nonbound genes ( COL1A1 ) remained unchanged after AS1842856 treatment. We also observed a significant inhibition of RORC and NR1D1 , core clock circadian genes that are dysregulated in OA (). PER1 is also a core clock circadian gene dysregulated in OA, but no significant effect was observed upon treatment with AS1842856.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Other predicted ECM genes bound by FoxO1 ( COL3A1 , COL5A2 ) and nonbound genes ( COL1A1 ) remained unchanged after AS1842856 treatment. We also observed a significant inhibition of RORC and NR1D1 , core clock circadian genes that are dysregulated in OA (). PER1 is also a core clock circadian gene dysregulated in OA, but no significant effect was observed upon treatment with AS1842856.…”
Section: Resultsmentioning
confidence: 67%
“…Previous findings from our group and others have shown that the circadian clock is disrupted in human OA () and that perturbation of the circadian clock promotes OA pathogenesis (). Furthermore, FoxO pathways are disrupted in OA (1) and have been linked to circadian rhythms ().…”
Section: Discussionmentioning
confidence: 75%
“…To frame the power of EV-miRNAs in the OA setting, the 818 target mRNAs were filtered through 2368 abundantly expressed genes, identified as laying in the first quartile of expression (out of 9474 total genes), in cartilage biopsies from OA patients [44]. After filtering, 224 EV-miRNA targets were left and shared ( Supplementary Table S3).…”
Section: Target and Effect Prediction Of Ev-mirnas On Oa-cartilagementioning
confidence: 99%
“…To evaluate the general expression profile of genes in OA, previously published gene expression datasets were analyzed by array and high throughput sequencing. The gene expression data of GSE114007 (32) and GSE117999 (33) were downloaded from the Gene Expression Omnibus (GEO) database (https://www.ncbi.nlm.nih.gov/geo). GSE114007 compared the genome-wide molecular profile of 20 patients with OA and 18 controls based on the GPL11154 (Illumina HiSeq 2000) and GPL18573 (Illumina NextSeq 500) platforms.…”
Section: Collection Of Serum Samples From Patients the Involvement Omentioning
confidence: 99%